Legal Analysis of Mastery and Ownership of Land Rights Arise in Rembang Regency - Laksono, Ruananda Kharismatika; Hasana, Dahniarti; Hafidz, Jawade (Jurnal Konstatering, 2023)
This study aims to determine the mechanism for acquiring land rights to land in Rembang, Pasar Baggi Village, and how the law is enforced over the ownership of the emerging land. The research method used is sociological juridical research. namely a legal research carried out by looking at aspects of the application of the law itself in society, or a study of community behavior that arises as a result of interacting with the existing system of norms. This research uses an empirical approach and a statutory approach. Research data used in this study are primary data and secondary data. The data collection technique is by conducting direct interviews with sources in the field and document studies. The results of this study indicate that the mechanism for obtaining land rights arising in Rembang Regency is still based on local customary law/customs. This is proven because there are no people who have permission directly from the authorized government apparatus, namely the Rembang District Land Office. According to legal provisions in a formal juridical manner, in principle, the steps that must be taken to obtain land rights are the same as applications for state land rights in general, but for land arising on the coast, you must see regulations relating to land tenure in coastal areas and spatial plans. So far the Rembang Regency Land Office has not conducted an inventory of emerging land as mandated in the Circular of the Minister of Agrarian Affairs/Head of National Land Agency Number 410-1923 concerning Controlling the Status of Emerging Land and Reclamation. Meanwhile, the people who control the emerging land have not yet reported the emerging land they control. This shows that the government and the local community have not fully implemented the applicable laws and regulations, so that it can be said that the law enforcement of emerging land tenure in Rembang Regency has not run optimally. Keywords: Acquisition; Agrarian; Land.